OPTIMALISASI PRODUKTIVITAS DAN KUALITAS BASRENG BERBASIS AUTOMATIC OIL DRAINER MACHINE TECHNOLOGY PADA UMKM DELLA MUDA - Soenar Soekopitojo; Sujito, Sujito; Ilham Ari Elbaith Zaeni; Dyah Lestari; Revanza Akiella Jihan Putra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Basreng (fried meatballs) is one of popular Sundanese snacks that is highly favored by the Indonesian people. Its savory flavor, crunchy texture, and long shelf life make it a favorite snack choice among various groups. In Madiredo Village, Pujon District, Malang Regency, there is a micro, small, and medium enterprise (MSME) called Della Muda, led by Atik Muda. This MSME has a unique innovation in producing basreng made from vegetables, with a production capacity of up to 30 kilograms per batch. However, in practice, the business faces challenges during the oil-draining stage, which is still done manually. This process not only takes a considerable amount of time but can also affect the final quality of the product, such as its texture and shelf life.As a solution to this problem, appropriate technology in the form of an Automatic Oil Drainer Machine is applied. This technology works on the principle of centrifugal force, which can speed up and optimize the oil-draining process from fried products. The machine is designed using food-grade stainless steel material, which is rust-resistant, easy to clean, and safe for use in both household and small-scale industries. The implementation of this machine is expected to make the production process more efficient and improve product quality. This will certainly have a positive impact on increasing the productivity of Della Muda MSME, maintaining the consistency of taste and texture of basreng, and indirectly supporting the economic growth of the surrounding community through the strengthening of local businesses based on technological innovation.